Is cohabitation an alternative to marriage? - Abd Malek, Normi (Elsevier Ltd, 2016)
In many countries in the world, the number of people resorting to cohabitation is increasing. In the USA, for example, the number of couples involved with cohabitation reached 7.8 million in 2012 while in the United Kingdom the number was 2.9 million in 2010. In Malaysia, the trend to cohabit is also increasingly common and accepted. The question arises whether this practice brings benefit to the parties involved as well as to the children. This paper highlights, to what extent, cohabitation brings an impact to the parties concerned as well as society in general from various aspects, including religious, legal, psychological and sociological.